2022
DOI: 10.1371/journal.pgen.1010372
|View full text |Cite
|
Sign up to set email alerts
|

Widespread employment of conserved C. elegans homeobox genes in neuronal identity specification

Abstract: Homeobox genes are prominent regulators of neuronal identity, but the extent to which their function has been probed in animal nervous systems remains limited. In the nematode Caenorhabditis elegans, each individual neuron class is defined by the expression of unique combinations of homeobox genes, prompting the question of whether each neuron class indeed requires a homeobox gene for its proper identity specification. We present here progress in addressing this question by extending previous mutant analysis o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 105 publications
(210 reference statements)
4
22
0
Order By: Relevance
“… (A) Dim expression of eat-4(syb4257) in head neurons ASK and ADL is consistent with previous fosmid-based reporter expression. RIC expression is consistent with previous observation using the same reporter allele (R eilly et al . 2022).…”
Section: Resultssupporting
confidence: 92%
“… (A) Dim expression of eat-4(syb4257) in head neurons ASK and ADL is consistent with previous fosmid-based reporter expression. RIC expression is consistent with previous observation using the same reporter allele (R eilly et al . 2022).…”
Section: Resultssupporting
confidence: 92%
“…This is based on our finding that the loss of a single HDTF (Bsh) results in reduced lamina neuron diversity (only L1-3), which may represent a simpler ancestral brain. A similar observation was described in C. elegans where the loss of a single terminal selector caused two different neuron types to become identical, which was speculated to be the ancestral ground state (Arlotta and Hobert, 2015; Cros and Hobert, 2022; Reilly et al, 2022), suggesting phylogenetically conserved principles observed in highly distinct species. An interesting possibility is that evolutionarily primitive insects, such as silverfish (Truman and Riddiford, 1999), lack Bsh expression and L4/L5 neurons, retaining only the core motion detection L1-L3 neurons.…”
Section: Discussionsupporting
confidence: 66%
“…Terminal selector HDTFs not only drive the expression of neuron functional identity genes but also activate pan-neuronal genes (Hobert, 2021; Howell et al, 2015; Kratsios et al, 2015; Stefanakis et al, 2015). Loss of terminal selector HDTFs frequently results in altered neuronal identity and function (Arlotta and Hobert, 2015; Cros and Hobert, 2022; Reilly et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While most TTFs are not maintained in neurons, their function is likely maintained by another TF, e.g., HDTF, which is persistently expressed in neurons. Indeed, HDTFs function as terminal selectors and control the expression of neuronal identity genes (Cros and Hobert, 2022;Hobert, 2021;Howell et al, 2015;Reilly et al, 2022Reilly et al, , 2020. The primary HDTF Bsh specifies L4 and L5 neuronal fates (Xu et al, 2023).…”
Section: Discussionmentioning
confidence: 99%